2002
DOI: 10.1590/1809-43922002321174
|View full text |Cite
|
Sign up to set email alerts
|

Camu-camu: um fruto fantástico como fonte de vitamina C1

Abstract: Resumo -Analisou-se o teor de vitamina C em três acessos de camu-camu coletados na região leste do Estado de Roraima, sendo um no rio Maú, e outros dois (uma planta isolada e outra população) no rio Urubu, ambos afluentes do rio Tacutu. Para a determinação de ácido ascórbico utilizou-se HPLC. De acordo com os resultados obtidos, verificou-se que os frutos coletados de uma planta individual situada no rio Urubu apresentaram as maiores concentrações de ácido ascórbico 6112±137,5 mg em 100g (polpa). As populações… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
33
2
36

Year Published

2015
2015
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 63 publications
(78 citation statements)
references
References 1 publication
7
33
2
36
Order By: Relevance
“…These values agree with those reported in Peru by Imán et al (2011a) for 43 camu-camu subsamples of the Germplasm Bank of the Brazilian institute of agricultural research INIA, with a mean of 11.47 g. Similar results were reported by Yuyama (2002), with mean values between 9.46 and 11.35 g of the different subsamples. Mean values of 10 g were also reported by Inga et al (2001).…”
Section: Analysis Of Variancesupporting
confidence: 91%
See 3 more Smart Citations
“…These values agree with those reported in Peru by Imán et al (2011a) for 43 camu-camu subsamples of the Germplasm Bank of the Brazilian institute of agricultural research INIA, with a mean of 11.47 g. Similar results were reported by Yuyama (2002), with mean values between 9.46 and 11.35 g of the different subsamples. Mean values of 10 g were also reported by Inga et al (2001).…”
Section: Analysis Of Variancesupporting
confidence: 91%
“…However, the levels differed, and were significantly higher in this study than reported elsewhere , Pinedo et al 2004, Smiderle and Souza 2008, Imán et al 2011b. On the other hand, these values are in line with those observed by Yuyama (2002), who describe that higher AA levels were extracted from the pulp plus skin portion of plants in the State of Roraima; the highest content was found in populations from the Urubu river (5737±236.1 mg). The values recorded for AA identified populations and subsamples with better performance for this trait.…”
Section: Roraimasupporting
confidence: 91%
See 2 more Smart Citations
“…Each fruit has one to four, more commonly two to three, kidneyshaped, ellipsoid seeds covered with fibril filaments [2]. Interest in camu-camu has grown because of its notable vitamin C content, varying from 1600 to 2994 mg/100g of pulp [3] Even higher concentrations were found by in three camu-camu batches from east Roraima, 3571 to 6112 mg/100g of pulp, making it the fruit with the highest vitamin C content in the world [4].…”
Section: Introductionmentioning
confidence: 99%